APPLICATION OF THE ELECTROPHORESIS OF COTYLEDON PROTEINS AND ISSR-MARKERS TO THE IDENTIFICATION OF HYBRIDS BETWEEN SORBUS SIBIRICA HEDL. AND SORBOCOTONEASTER POZDNJAKOVII POJARK. - S. V. Asbaganov; E. V. Kobozeva; A. V. Agafonov (Вавиловский журнал генетики и селекции)
It is shown that cotyledon protein SDS-electrophoresis and inter-simple sequence repeat DNA markers (ISSRs) can be used in identification of hybrid genotypes in Sorbus sibirica Hedl. and Sorbocotoneaster pozdnjakovii Pojark. hybridization. Recombination of molecular and morphological characters was observed in hybrids, which proves close relationships of the parental genomes and, as a consequence, the potential of utilizing Sorbocotoneaster pozdnjakovii genotypes in breeding of Sorbus cultivars. The results confirm that the genus Sorbocotoneaster arose as a result of Sorbus and Cotoneaster hybridization.